Study on microstructural and mechanical properties of cementitious materials composed of fly ash and dacite powder - Liu, Lu; Tan, Jianjun; Qiu, Huanfeng; Zhang, Jianbo; Guo, Yong (Frontiers in Materials, 2024)
The hydration reaction of mass concrete seriously endangers the structural safety. At present, the concrete production relies excessively on fly ash due to hydration reaction. In view of the problem that the demand of fly ash exceeds the supply, this paper proposes to use dacite powder to partially replace fly ash as the raw material for preparing cementitious materials. Through comprehensive tests and microstructure tests, various properties of dacite powder and fly ash composite cementitious materials are studied. The results show that: 1. The dacite powder with a specific surface area of 650m 2 /kg, a fineness of 15% under laser particle size and a ball-milling time of 1.0 h has the best performance. 2. It is advisable to mix dacite powder and fly ash. The total amount of dacite powder should not exceed 30% of the cementitious material. It has the best performance when the amount of dacite powder and fly ash is the same. 3. The alkali activity of aggregate can hardly be inhibited by mixing dacite powder alone. The recommended measures to inhibit the alkali activity of aggregate are: (i) mixing more than 20% fly ash alone. (ii) mixed with 25% dacite powder and more than 15% fly ash.